Metabolic Profiling Reveals Aggravated Non-Alcoholic Steatohepatitis in High-Fat High-Cholesterol Diet-Fed Apolipoprotein E-Deficient Mice Lacking Ron Receptor Signaling - Allen, Joselyn N. (Metabolites, 2020)
Non-alcoholic steatohepatitis (NASH) represents the progressive sub-disease of non-alcoholic fatty liver disease that causes chronic liver injury initiated and sustained by steatosis and necroinflammation. The Ron receptor is a tyrosine kinase of the Met proto-oncogene family that potentially has a beneficial role in adipose and liver-specific inflammatory responses, as well as glucose and lipid metabolism. Since its discovery two decades ago, the Ron receptor has been extensively investigated for its differential roles on inflammation and cancer. Previously, we showed that Ron expression on tissue-resident macrophages limits inflammatory macrophage activation and promotes a repair phenotype, which can retard the progression of NASH in a diet-induced mouse model. However, the metabolic consequences of Ron activation have not previously been investigated. Here, we explored the effects of Ron receptor activation on major metabolic pathways that underlie the development and progression of NASH. Mice lacking apolipoprotein E (ApoE KO) and double knockout (DKO) mice that lack ApoE and Ron were maintained on a high-fat high-cholesterol diet for 18 weeks. We observed that, in DKO mice, the loss of ligand-dependent Ron signaling aggravated key pathological features in steatohepatitis, including steatosis, inflammation, oxidation stress, and hepatocyte damage. Transcriptional programs positively regulating fatty acid (FA) synthesis and uptake were upregulated in the absence of Ron receptor signaling, whereas lipid disposal pathways were downregulated. Consistent with the deregulation of lipid metabolism pathways, the DKO animals exhibited increased accumulation of FAs in the liver and decreased level of bile acids. Altogether, ligand-dependent Ron receptor activation provides protection from the deregulation of major metabolic pathways that initiate and aggravate non-alcoholic steatohepatitis.